Globus Pallidus Externus Neurons Expressing parvalbumin Interconnect the Subthalamic Nucleus and Striatal Interneurons - Saunders, Arpiar (PLoS One, 2016)
The globus pallidus externus (GP) is a nucleus of the basal ganglia (BG), containing GABAergic projection neurons that arborize widely throughout the BG, thalamus and cortex. Ongoing work seeks to map axonal projection patterns from GP cell types, as defined by their electrophysiological and molecular properties. Here we use transgenic mice and recombinant viruses to characterize parvalbumin expressing (PV(+)) GP neurons within the BG circuit. We confirm that PV(+) neurons 1) make up ~40% of the GP neurons 2) exhibit fast-firing spontaneous activity and 3) provide the major axonal arborization to the STN and substantia nigra reticulata/compacta (SNr/c). PV(+) neurons also innervate the striatum. Retrograde labeling identifies ~17% of pallidostriatal neurons as PV(+), at least a subset of which also innervate the STN and SNr. Optogenetic experiments in acute brain slices demonstrate that the PV(+) pallidostriatal axons make potent inhibitory synapses on low threshold spiking (LTS) and fast-spiking interneurons (FS) in the striatum, but rarely on spiny projection neurons (SPNs). Thus PV(+) GP neurons are synaptically positioned to directly coordinate activity between BG input nuclei, the striatum and STN, and thalamic-output from the SNr.